Concept maps in reading comprehension in second-year high school students from educational institution N ° 7259 “Víctor Raúl Haya de la Torre” Pachacámac - Almanza Cori, Marco Antonio (2018)
The scientific investigation that has been realized it is basic, correlacional not experimental grounds, the factors of study are two: the conceptual map like educational technologies in the reading comprehension of the Educational Institution N º 7259 " Víctor Raúl Haya of the Tower " - Pachacámac. The design of the investigation is transactional, correlacional, grounds, bivariada, cross street. The instruments expire with the qualities of validity and reliability. The study raises the following hypothesis of investigation significant relation exists between them s conceptual maps and the reading comprehension of the students of the fourth degree of secondary education of the area of Communication in " Víctor Raúl Haya of the Tower " Pachacámac, Lima, Peru, 2013. The obtained results allow to reject the void hypothesis and to accept the hypothesis investigated so Rho de Spearman has met on having applied the formula a level of significancia of 95 % one thought that the coefficient of correlation Rho de Spearman is of 0,828 and p_ value is of 0,000 therefore we establish that a level has correlation very well, see that there exists a direct relation and a level of significancia minor who 0,05 for such a motive rejects the Void hypothesis and the alternate one is accepted.